Magnetization switching driven by magnonic spin dissipation - Won-Young Choi; Jae-Hyun Ha; Min-Seung Jung; Seong Been Kim; Hyun Cheol Koo; OukJae Lee; Byoung-Chul Min; Hyejin Jang; Aga Shahee; Ji-Wan Kim; Mathias Kläui; Jung-Il Hong; et al. (Nature Communications)
Abstract Efficient control of magnetization in ferromagnets is crucial for high-performance spintronic devices. Magnons offer a promising route to achieve this objective with reduced Joule heating and minimized power consumption. While most research focuses on optimizing magnon transport with minimal dissipation, we present an unconventional approach that exploits magnon dissipation for magnetization control, rather than mitigating it. By combining a single ferromagnetic metal with an antiferromagnetic insulator that breaks symmetry in spin transport across the layers while preserving the symmetry in charge transport, we realize considerable spin-orbit torques comparable to those found in non-magnetic metals, enough for magnetization switching. Our systematic experiments and comprehensive analysis confirm that our findings are a result of magnonic spin dissipation, rather than external spin sources. These results provide insights into the experimentally challenging field of intrinsic spin currents in ferromagnets, and open up possibilities for developing energy-efficient devices based on magnon dissipation.